Evaluating Health benefits of wheat flatbreads with different fruit peels: determination of anti-oxidant, nutritional value and sensory characteristics - Tehreem, Sana; Abbas, Muhammad; uddin, Zia; Khan, Imran; Nayab, Durri; Shah, Maria (International Journal of Pathology, 2024)
Background: Fruit peels including pomegranate, orange and lemon are rich sources of antioxidant and other bioactive compounds. These fruit peels can be utilized for many health benefits. Methods: The current study was to determine the nutritive value, antioxidant activity and sensory characteristics of wheat flatbread incorporated with pomegranate, orange and lemon peels. The incorporated flatbreads (chappati/roti) were made by replacing wheat flour with 5% of peels powder of each fruit. Results: The data revealed that addition of fruit peels powder increased the moisture, ash, fats and fiber contentsbut reduced the protein and carbohydrate contents of the flatbreads. The minerals analysis showed that lemon peel incorporated flatbreadhad significantly the highest amounts of calcium, magnesium, sodium and chromium (p<0.05). Similarly, the orange flatbread was relatively superior in iron content only, whereas, the pomegranate had relatively lower minerals content except magnesium. The total phenolic content and antioxidant activity of flatbreads was also increased with incorporation of peels powder. All the sensory attributes of all the incorporated flatbreads were in the acceptable range. Conclusion: It is recommended that the utilization of peels of citrus fruits as food additive should be encouraged to get potential nutritional and health benefits of the peels. This can be utilized for health benefits in variety of diseases.